Water and nutrient use efficiencies of potato-based (Solanum tuberosum L.) rotation systems in North West Province, South Africa - Steyn, Joachim Marthinus (University of Pretoria, 2024)
Dissertation (MSc Agric (Soil Science))--University of Pretoria, 2019.